Acht grafvondsten van de Veluwse klokbekergroep als uitgangspunt voor chronologische beschouwingen over de relaties saalisch-böhmische Schnurkeramik, Enkelgrafcultuur, Klokbeker-Oostgroep en Nederlands-Westduitse klokbekergroepen - Lanting, J. N. (Barkhuis Publishing, 2013)
In the 1920s and 1930s, in addition to professional archaeologists from Leiden and Groningen, several amateur archaeologists were also active on the Veluwe, including a number of professional soldiers. Two of them, Captain H.J. Calling from Ede and sergeant H. Westendorp from Nieuw-Milligen, get more attention here. That's partly because of their finds, partly because of the documentation accompanying those finds. Bellen made notes in pocketbooks, Westendorp corrected errors in the description of his collection in Bursch's dissertation. Bellen and Westendorp excavated six grave finds with copper tongue daggers. These have been described before, but are discussed again here using all available documentation, and in two cases with data from additional soil investigations. In addition, two accidental finds from sand/gravel quarries are discussed, one with a golden hair ornament, the other with a decorated earthenware bowl on four column-shaped feet. It is shown that such old amateur excavations and accidental finds are worthy of a new study. In the second part of this book, the eight finds are placed in a broader context. Based in part on 14C dates and a few more recent finds of gold hair jewelry in Beers-Gassel (N. Br.) and Eelde (Dr.), it is shown that objects such as copper tongue daggers, gold/silver Lockenringe and foot scales, which are considered characteristic for the Bell Beaker culture, are derived from the saalische Schnurkeramik, partly directly, partly via the Single Grave culture.